A comparative analysis of health indicators in India and Madhya Pradesh using NFHS-4 and NFHS-5 data - Jagmohan Singh Dhakar; Sanjay Jain; Vishakha Chanchal; Santosh Babu; Deepak Dhakar (International Journal Of Community Medicine And Public Health, 2026)
Background: The national family health survey (NFHS) provides important evidence for monitoring health indicators in India. This study compared changes between NFHS-4 (2015–16) and NFHS-5 (2019–21) for India and Madhya Pradesh. Methods: Key health indicators were compared using descriptive statistics, Wilcoxon Signed Rank, Mann–Whitney U, Kruskal–Wallis, Spearman’s correlation, and regression analysis. Coefficients of variation were also assessed to examine changes in variability. Results: Mean health indicator scores increased from 38.12 to 40.81 in India and from 37.52 to 40.72 in Madhya Pradesh. Improvement was statistically significant for India (Z=2.611, p=0.009), but not for Madhya Pradesh (Z=1.576, p=0.115). The magnitude of improvement did not differ significantly between India and Madhya Pradesh (Z=−0.133, p=0.894). No significant domain-wise variation in percentage change was observed for India (p=0.280) or Madhya Pradesh (p=0.212). Strong positive correlations were observed between India and Madhya Pradesh in NFHS-4 (r=0.936) and NFHS-5 (r=0.968). Baseline NFHS-4 values did not significantly predict subsequent improvement in India (R²=0.011, p=0.455) or Madhya Pradesh (R²=0.048, p=0.120). Variability increased over time. Conclusions: India showed significant improvement, while Madhya Pradesh demonstrated positive but non-significant progress. Increasing variability highlights persistent disparities, emphasizing the need for targeted and region-specific interventions to achieve equitable health improvements.